Effects of Exhibitors' Trade Show Participation on market performance: longitudinal research. Issue 12 (1st December 2020) - Kim, Bong-Seok; Kim, Kyoung-Bae; Park, Changwon; Lee, Jiyeon
ABSTRACT: This study proposed a structural model capturing the exhibitor's internal resources, a trade show (TS) outputs and domestic market and international export performance derived from the conceptual framework underpinning the resource-based theory. Longitudinal analysis is applied to determine how TS output affects market performance over time after the conclusion of the TS. The results showed that the exhibitor's resources partially affected TS output and market performance and that TS output influenced market performance differently over time after the TS ended. By providing a better understanding of market performance in a TS context, this paper enriches research on TS issues.